Glycemic index, glycemic load, and lung cancer risk: A meta-analysis of cohort and case-control studies. - Hongzhen Du; Tianfeng Zhang; Xuning Lu; Meicui Chen; Xiaoling Li; Zengning Li (PLoS ONE)
Objective Glycemic index (GI) or glycemic load (GL) has been investigated in the field of cancer research for several years. However, the relationship between GI or GL and lung cancer risk remains inconsistent. Therefore, this study aimed to summarize previous findings on this relationship. Methods PubMed, Embase, Scopus, Web of Science databases, and Cochrane Library were searched by July 2021. This review was conducted in accordance with the PRISMA guidelines. A fixed or random-effects model was adopted for meta-analysis to compute the pooled relative risks (RR) and their corresponding 95% confidence intervals (CIs). Subgroup analyses, sensitivity analyses, and publication bias analyses were also performed. Results In total, nine articles were included, with four case-control studies and five cohort studies, including 17,019 cases and 786,479 controls. After merging the studies, pooled multivariable RRs of lung cancer based on the highest versus the lowest intake were 1.14 (95%CI: 1.03-1.26) and 0.93 (95%CI: 0.84-1.02) for GI and GL. Results persisted in most stratifications after stratifying by potential confounders in the relationship between GI and lung cancer risk. There was a non-linear dose response relation for GI with lung caner risk. Conclusion GI typically has a positive relationship with lung cancer risk. However, no associations between GL and lung cancer risk were observed based on current evidence, suggesting that this issue should be studied and verified further to substantiate these findings.